38.4k views
20 votes
-2 • (-3)3 = ?

i really need help, I’m struggling so much in math.

-2 • (-3)3 = ? i really need help, I’m struggling so much in math.-example-1
User Yankee
by
5.9k points

2 Answers

7 votes

Let's break this statement into small pieces. Let's start with
(-3)^(3). This means
-3 * -3 * -3 which is equal to
-27 (
-3 * -3 = 9, 9 * -3 = -27).

Note the following rules


  • - * - = +

  • + * + = +

  • - * + = -

  • + * - = -

Now let's solve the rest of the equation.
-2 \cdot (-3)^(3) = -2 \cdot -27 (Note
\cdot is the same as
*.
= -2 \cdot -27,
54

The answer is
54

User Brendangibson
by
6.7k points
6 votes

Answer:

The answer would be 54

Explanation:

User Ablerman
by
5.6k points